Faktor-Faktor Yang Mempengaruhi Dividend Payout Ratio Pada Perusahaan Perbankan Di BEI - Sasmito Walaa Rico Prakoso; Susy Muchtar (Jurnal Ekonomi, 2023)
The dividend policy considers whether a company's earnings will be reinvested or distributed. This policy significantly impacts stakeholders' interests. For investors, the dividend policy is crucial because it affects the level of return on investment. This study aims to explain and analyze whether the bank size, return on assets (ROA), debt-to-equity ratio (DER), loan-to-debt ratio (LDR), and net interest margin (NIM) have a significant impact on the dividend payout ratio (DPR). The sample for this research consists of 10 banking companies listed on the Indonesia Stock Exchange from 2018 to 2022, encompassing 50 observations. The sample was tested through descriptive statistical analysis, model selection tests, and panel data regression analysis. The research findings indicate that Bank Size has a positive and significant impact on the DPR, ROA has a negative and significant impact on the DPR, while DER, LDR, and NIM do not significantly influence DPR.